2018
DOI: 10.1097/jfn.0000000000000215
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Introduction of the Safewards Model to a Medium- to Long-Term Forensic Mental Health Ward

Abstract: Care and treatment in forensic mental health wards can present with challenges when loss of hope and freedom, and aggression are present, which can then influence ward atmosphere and feelings of safety. Safewards is a model designed to address a range of conflict (e.g., aggression and self-harm) and containment (e.g., use of restrictive interventions) events and may provide a suitable approach to delivery of care in a forensic setting, while also addressing aggression, restrictive interventions, and ward atmos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
135
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(139 citation statements)
references
References 23 publications
2
135
0
Order By: Relevance
“…Participants overall reported feeling safer, and participants who rated the model and interventions as excellent reported one of the key changes was that the ward felt calmer, which led to them feeling safer. This finding concurs with reports of consumers from a forensic mental health ward who stated that the ward was calmer and they felt safer after the implementation of Safewards (19).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Participants overall reported feeling safer, and participants who rated the model and interventions as excellent reported one of the key changes was that the ward felt calmer, which led to them feeling safer. This finding concurs with reports of consumers from a forensic mental health ward who stated that the ward was calmer and they felt safer after the implementation of Safewards (19).…”
Section: Discussionsupporting
confidence: 89%
“…Respect from staff for participants and between the consumers was important in the feedback provided and mirrors the findings of Maguire et al (19), who reported that both consumers and staff felt increased respect between the two groups (30). Participants in our study reported that Clear Mutual Expectations and the Mutual Help Meetings played a part in increasing the feeling of respect from staff for participants.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Problems with implementation have included low adherence (fidelity) and lack of staff acceptance of the model (33, 34). This contrasts with high fidelity to the model in some settings, resulting in reduction in conflict events (35) and reduction in the use of forced sedation (36). Hence, high fidelity to the model is important to its outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…One such programme is the Safewards model, providing 10 interrelated interventions (Bowers 2014;Bowers et al 2014). Although several studies on Safewards showed significant reductions in conflict events, no cost-effective studies were performed (Bowers et al 2015;Fletcher et al 2017;Maguire et al 2018;Baumgardt et al 2019). Depending on the available staff capacity, costs in terms of money and budget may be smaller or larger than the costs we estimated in this analysis.…”
Section: Discussionmentioning
confidence: 93%